Architectural details - doors - Braun, Markus Sebastian ([S.l.] : Verlagshaus Braun, 2002)
Doors are prominent and essential elements of all buildings. They pave the way into and out of a building. Thus, doors are simultaneously an article of daily use and an explicit statement of the homeowner. They can serve as an invitation just as well as a.
Keywords: Doors -- Europe